INTerest of electrophysiological and functional EXploration in the evaluation of symptomatic impact of superior semicircular canal DEHIscence syndrome (INTEX-DEHI study): Study protocol for a reliability and validity study - Quentin Legois; Fabrice Giraudet; Yohan Gallois; Benoit Lepage; Eugen Ionescu; Jean-François Vellin; Valérie Franco-Vidal; Akil Kaderbay; Marie-Jeanne Vellin; Mathieu Marx (PLoS ONE, 2025)
Background Interest in Superior Semicircular Canal Dehiscence (SSCD) has increased, but its diagnosis and management remain challenging. Despite advances in imaging and electrophysiological tests, many patients face long diagnostic delays and significant distress due to unclear symptom severity. While some patients show no symptoms despite radiological evidence, others experience disabling effects. This research aims to bridge the gap between objective tests and symptom severity, improving the understanding and management of SSCD. Methods This is a prospective, non-randomized, longitudinal observational clinical study including repeated measures. It is part of the inter-regional hospital research program “INTEX-DEHI”, involving five university hospitals. Patients diagnosed with unilateral superior semicircular canal dehiscence via CT scan will be followed over four weeks with three visits spaced 15 days apart. The main objective is to describe the clinical and paraclinical characteristics of SSCD and analyze their correlation. Electrophysiological, functional, and clinical measurements will be collected at each visit. Discussion The relationship between electrophysiological tests and the symptomatic impact of superior semicircular canal dehiscence remains underexplored. This research aims to bridge this gap by studying both common and specific VEMP frequencies, as well as EcoG and WBT, to assess their sensitivity, specificity, and diagnostic value. While this study proposes innovative tools to objectively assess symptoms, challenges remain, particularly the underdiagnosis of the syndrome and selection biases, especially in patients with fluctuating symptoms. Additionally, the diversity of clinical presentations and the absence of symptoms in some patients complicate the interpretation of results. Trial registration Clinicaltrials.gov, NCT06170398.